Sacral buildings suitable for defense purposes and their ensembles in Vilnius in the 14th-18th centuries - Linas Girlevičius (Lietuvos Istorijos Studijos)
In the 14th-18th centuries, Vilnius had a number of sacral buildings adapted for defense purposes as well as ensembles of those buildings. This group of objects of the defense heritage is one of the components of the defense system of Vilnius. The analysis of the previous and the latest data has shown that the number of this kind of objects is much bigger than it has been assumed. Still, it is hypothetical whether some of them really belong to the group of defense heritage objects. A number of sacral buildings and their groups were established in places that were important in terms of the defense of Vilnius as early as in the 14th and 15th centuries. Relics of the early fortifications have remained in the territories of several sacral objects. The greater part of sacral buildings and monasteries discussed in the article were deliberately established in places that were important to the defense of the city and its environs, and quite a few were constructed by order of the ruler (Grand Duke of Lithuania and/or King of the Polish-Lithuanian State).